2016
DOI: 10.1186/s12955-016-0572-x
|View full text |Cite
|
Sign up to set email alerts
|

Diet and physical activity in people with intermediate cardiovascular risk and their relationship with the health-related quality of life: results from the MARK study

Abstract: BackgroundTo analyze the interplay between diet, physical activity and health-related quality of life in a Spanish randomly selected sample of individuals attended in general practitioners offices with intermediate cardiovascular risk.MethodsThis study analyzed 314 subjects, aged 35–74 years (50.6% women), from the MARK study, conducted in Spain. Health related quality of life was measured by the SF-12 questionnaire. The assessment of the lifestyles included the diet quality index, the adherence to the Mediter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…The magnitude of the association declined slightly when we adjusted for the covariates, but the significance remained stable ( p < 0.05). These results follow in the tradition of previous studies that have found positive links between the Mediterranean diet and health in older adults [ 27 , 28 , 29 ], though ours has implications for Europe in general with the use of our broadly-scoped sample. The results were also robust when we calibrated the composition of our Mediterranean diet variable to slightly reduce the frequency of meats and legumes consumption, where we even observed a higher level of significance ( p < 0.01) and magnitude in relation with the level of depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The magnitude of the association declined slightly when we adjusted for the covariates, but the significance remained stable ( p < 0.05). These results follow in the tradition of previous studies that have found positive links between the Mediterranean diet and health in older adults [ 27 , 28 , 29 ], though ours has implications for Europe in general with the use of our broadly-scoped sample. The results were also robust when we calibrated the composition of our Mediterranean diet variable to slightly reduce the frequency of meats and legumes consumption, where we even observed a higher level of significance ( p < 0.01) and magnitude in relation with the level of depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, there is evidence of an association between quality of life and healthy lifestyles (Koltyn, ; Munoz, Fito, Marrugat, Covas, & Schroder, ; Stephens, ). This is supported by our earlier study where perceived quality of life was associated with food habits and physical activity in a large sample of adults with intermediate cardiovascular risk (Sanchez‐Aguadero et al., ).…”
Section: Introductionsupporting
confidence: 79%
“…The studies measured the association of dietary patterns derived from a priori dietary indexing methods or empirical approaches or both with QoL in older adults. While nine studies [ 21 , 66 , 68 , 71 , 73 , 74 , 75 , 76 , 77 ] measured baseline association between dietary patterns and QoL, four studies measured diet at baseline and QoL at both baseline and/or follow up [ 22 , 67 , 70 , 72 ], one study measured both diet and QoL at multiple points in the study [ 69 ] and one study measured the association of change in dietary patterns made in relation to a chronic disease diagnosis and its impact on QoL [ 72 ]…”
Section: Resultsmentioning
confidence: 99%